Mutations in the Drosophila Neuroglian cell adhesion molecule affect motor neuron pathfinding and peripheral nervous system patterning. - Hall, S.G.; Bieber, A.J. (Journal of Neurobiology, 1997)
We have identified and characterized three embryonic lethal mutations that alter or abolish expression of Drosophila Neuroglian and have used these mutations to analyze Neuroglian function during development. Neuroglian is a member of the immunoglobulin superfamily. It is expressed by a variety of cell types during embryonic development, including expression on motoneurons and the muscle cells that they innervate. Examination of the nervous systems of neuroglian mutant embryos reveals that motoneurons have altered pathfinding trajectories. Additionally, the sensory cell bodies of the peripheral nervous system display altered morphology and patterning. Using a temperature-sensitive mutation, the phenocritical period for Neuroglian function was determined to occur during late embryogenesis, an interval which coincides with the period during which neuromuscular connections and the peripheral nervous system pattern are established.